Exploring the characteristics of transfer pricing systems across countries - Alex Augusto Timm Rathke; Amaury José Rezende (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyses the characteristics of transfer pricing systems across countries, in order to identify the grouping structures intrinsically related with rules' similarities, and to explore the key characteristics revealed by each group. Applying hierarchical agglomerative technique for comparison of an extensive set of attributes from domestic transfer pricing regulations, we find substantial differences among transfer pricing rules thus to support the segregation of three major groups of countries. The variance across transfer pricing systems refers not only to formal tax provisions, but also to practical requirements and regular actions from authorities, and to governments' openness for discussion of unclear tax positions. Although most regulations follow the main guidelines established by OECD, additional unilateral mechanisms remain, suggesting that countries face distinct profit shifting occurrences and need to create specific measures in attempt to restrain it. It thus implies the existence of gaps in current transfer pricing guidelines, and reinforces the call for new anti-shifting mechanisms to cover a broader set of shifting arrangements.
Keywords: F23; H26; K34; 330; profit shifting; transfer pricing systems; BEPS; Transfer pricing